Human Capital and Saving Relationship - Murat İstekli; Alihan Serdengeçti (İktisat Politikası Araştırmaları Dergisi)
Human capital which can be expressed as the accumulation of knowledge and skills needed in producing economic value is one of thebasic production factors of a country. Saving is an economic indicator that is generally explained based on consumption behavior. Various income hypotheses have developed different approaches to saving. Based on this, it is thought that there may be a relationship between the acceptance that human capital influences the income of the individual and human capital and savings. To demonstrate that human capital has a significant effect on saving rates, these two variables need to be analyzed. In this study, annual saving rates and human capital data of developing OECD countries such as South Africa, China, Hungary, Chile, Costa Rica, Mexico, Poland, Russia were analyzed using panel data analysis method. In these countries, the effect of the independent variable human capital on saving rates, which is the dependent variable, between 1996 and 2015 was examined. There is no other study examining the relationship between human capital and saving in terms of these countries in this period. As a result of the analysis, it was determined that the independent variable explained the dependent variable by 13%, and an increase of 1% in human capital increased savings by 8,36%. Developing countries should take human capital seriously to approach developed countries. To increase human capital, education policies should be reviewed seriously. The increase in human capital brings along economic development. Thus, positive results can be obtained in income distribution.